Green Approach for Decolorization and Detoxification of Textile Dye- CI Direct Blue 201 Using Native Bacterial Strains: DOI: 10.32526/ennrj.18.1.2020.01 - EMMS, Ekanayake; M. Manage, Pathmalal (Environment and Natural Resources Journal, 2019)
One hundred and fifty six native bacterial strains with different morphological characters were isolated from water and soil samples collected from textile wastewater effluent sites, Sri Lanka. Three isolated bacterial strains were more effective on decolorization of CI Direct Blue 201 textile dye and 16s rRNA analysis reveals that the bacterial strains were Alcaligenes faecalis (MK166784), Micrococcus luteus (MK166783) and Staphylococcus warneri (MK256311). A. faecalis, M. luteus and S. warneri showed complete decolorization of CI Direct Blue 201 textile dye within 60, 64, and 72 h of incubation time respectively under the static conditions at 28 oC. Decolorization was effective at a temperature range from 24 oC to 40 oC and pH range from 7 to 9. The presence of tryptone, peptone or yeast in the Mineral Salt Medium enhanced the decolorization of the dye. Phytotoxicity assay based on the seed germination percentages of Oryza sativa and Vigna radiate showed that the detoxification of CI Direct Blue 201 textile dye after the bacterial treatment was effective signifying the potential applicability of the A. faecalis, M. luteus and S. warneri to develop a green application to treat textile wastewater.